Walküren, Bodbs, Sirenen - Egeler, Matthias (De Gruyter, 2011)
This work considers Valkyries in the medieval Scandinavian mythology and literature and places them in the context of the early history of European religion. Drawing on textual and archaeological sources, a detailed review of Celtic, Etruscan and Graeco-Roman female demons of the battlefield and of death is presented, and their remarkable similarity with the Valkyries analysed against the background of Mediterranean-transalpine cultural contacts.
Description based on publisher supplied metadata and other sources
Keywords: Religion; Mythologie; Kulturkontakt; Antike; Walküre; Mythos; Sagengestalt; Kulturvergleich; Altnordisch; Literatur